2015
DOI: 10.1155/2015/783149
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Pricing of a Web Service in an Advance Selling Environment

Abstract: Consider a web service with different quality of service levels where users may purchase their required web service through a reservation system. The service provider adjusts prices of web service classes over a prespecified time horizon to manage demand and maximize profit. Users may cancel their services as long as they pay a penalty. One of the important challenges for service providers is capacity limitation of the resources employed in offering the web service. Thus, taking this important proposition into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…There are little achievements addressing pricing problem of perishables in advance selling strategy. Safari et al (2015) developed a continuous time optimal control model for identifying pricing strategies for the web service classes based on maximum principle and proposed an algorithm to obtain the optimal pricing policy. From above literature review, we found that it is of great necessity to further carry out our research on pricing of perishable items with the consideration of an advance selling strategy.…”
Section: Review Of Previous Workmentioning
confidence: 99%
“…There are little achievements addressing pricing problem of perishables in advance selling strategy. Safari et al (2015) developed a continuous time optimal control model for identifying pricing strategies for the web service classes based on maximum principle and proposed an algorithm to obtain the optimal pricing policy. From above literature review, we found that it is of great necessity to further carry out our research on pricing of perishable items with the consideration of an advance selling strategy.…”
Section: Review Of Previous Workmentioning
confidence: 99%
“…Dynamic schemes models are believed to be more powerful and flexible than static pricing strategies and have been used in many areas of industry in addition to telecom (see rf. 5,6,7 ), such as retailing, manufacturing, airlines, and ebusiness 8,9 . To illustrate, well-known all-you-cansend (or flat rate) pricing policy is a static scheme in which the customer leases bandwidth at a fixed price for a fixed contract period 10,11 .…”
Section: Introduction and Motivationsmentioning
confidence: 99%